2016
DOI: 10.1080/10749357.2015.1110307
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Investigating the Influence of Strength Training on Quality of Life in Ischemic Stroke

Abstract: The results of this study indicate that there was an improvement in the measures of strength in EG, and that there was a correlation between improvements in strength and quality of life in these patients who had previously suffered a stroke at least one year prior to study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
0
26
0
6
Order By: Relevance
“…In addition, it was observed that the selected articles aimed at studying the lower limbs. Only the study reported by Aidar et al [25] involved both the upper and lower limbs. Among the most studied exercises are knee extensors and flexors, hip flexors, plantar flexors, and dorsiflexors, while bench press exercises are the most common for the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was observed that the selected articles aimed at studying the lower limbs. Only the study reported by Aidar et al [25] involved both the upper and lower limbs. Among the most studied exercises are knee extensors and flexors, hip flexors, plantar flexors, and dorsiflexors, while bench press exercises are the most common for the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been described as an important way to promote physical and psychosocial health [1,2,3], in special groups [4,5,6,7,8,9,10,11] and disabled people [12]. Among physical activities, strength training has gained greater attention with several studies indicating better physical and psychosocial indicators [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A partir disso, elaborar um método que possibilite a continuidade na prática de exercícios, tão importante para essa população, que seja eficaz e de baixo custo, possa ser uma estratégia interessante. 6,7 O uso de materiais como aparelhos de musculação, pesos livres e faixas elásticas são de uso comum para a prática de exercício físico e trazem resultados importantes na força muscular, capacidade funcional e composição corporal de adultos e idosos, inclusive para aqueles com sequelas após AVE. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] As faixas elásticas são materiais de fácil utilização para prática de exercícios. São portáteis, de baixo custo, com formato que permite uma diversidade de movimentos e muito utilizadas para desenvolvimento de força muscular.…”
Section: Introductionunclassified